2000
DOI: 10.1093/jexbot/51.352.1931
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CO2 and mycorrhiza effects on biomass allocation and nutrient uptake of nodulated pea (Pisum sativum L.) plants

Abstract: The effect of ambient and elevated atmospheric CO(2) on biomass partitioning and nutrient uptake of mycorrhizal and non-mycorrhizal pea plants grown in pots in a controlled environment was studied. The hypothesis tested was that mycorrhizae would increase C assimilation by increasing photosynthetic rates and reduce below-ground biomass allocation by improving nutrient uptake. This effect was expected to be more pronounced at elevated CO(2) where plant C supply and nutrient demand would be increased. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 44 publications
8
67
0
1
Order By: Relevance
“…This might be attributed to a dilution effect due to higher dry matter production in the AMF treatment. This result is in accordance with other studies (Hirata et al 1988, Gavito et al 2000. Note that interactions of AMF with biological N fixation were not included in our study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This might be attributed to a dilution effect due to higher dry matter production in the AMF treatment. This result is in accordance with other studies (Hirata et al 1988, Gavito et al 2000. Note that interactions of AMF with biological N fixation were not included in our study.…”
Section: Discussionsupporting
confidence: 94%
“…The experimental soil in our study showed moderate (2006) to high (2007) P, K, and Mg concentrations. In other experiments on nutrient acquisition of chickpea (Hirata et al 1988) and pea (Gavito et al 2000) under sterile soil conditions and high soil P levels, P and K concentrations were not improved by AMF inoculation.…”
Section: Discussionmentioning
confidence: 79%
“…Many studies have documented that elevated CO 2 has a positive effect on C 3 crops due to stimulation of photosynthesis (Ainsworth and Long 2005;Pacholski et al 2015) and may thus benefit AM fungal colonization (Rillig et al 1999). In turn, AM symbiosis may further increase C assimilation thereby stimulating growth of the host plant under elevated CO 2 (Gavito et al 2000;Baslam et al 2014). However, the combined effect of AM fungal inoculation and CO 2 elevation on the partitioning of C among different organs in wheat plants and its implications for plant N balance remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Root colonization with mycorrhizal fungi generally has positive effects on plant growth (Chalk et al, 2006) and mycorrhizal inoculation is frequently applied to increase crop plant productivity in agricultural systems (li et al, 2000oRtaS et al, 2003;oRtaS, 2010). Positive effects of mycorrhiza on plants include increases in height (hayman, 1986;hoekSema et al, 2010;SafapouR et al, 2011), biomass (VejSadoVa et al, 1993;mathuR and VyaS, 2000;Ramana et al, 2010), shoot:root ratio (gaVito et al, 2000;VeReSoglou et al, 2012), production of flowers (dodd et al, 1983;CaRey et al, 1992), and yield in crop plants such as Phaseolus vulgaris, Glycine max, and Triticum aestivum (VejSadoVa et al, 1993;BethlenfalVay et al, 1997;aBdel-fattah, 1997;li et al, 2005;Ramana et al, 2010;SafapouR et al, 2011). There is an extensive body of literature on the effects of mycorrhizal fungi in a broad range of plant families including legumes (BaRea and azConaguilaR, 1983;yang et al, 1994;olSen et al, 1999a;1999b;liu et al, 2003;SCheuBlin and Ridgway, 2004;oRtaS, 2008;muleta, 2010) but a detailed understanding of costs and benefits arising from the mycorrhizal symbiosis under different abiotic conditions is often lacking.…”
Section: Introductionmentioning
confidence: 99%